Audio Visual Media about The Importance of Vulva Hygiene Increases The Knowledge of Pregnant Women - Andriansyah, Andriansyah; Refi, Weni Guslia; Herlina, Nina (Universitas Andalas, 2023)
Pregnant women tend to experience vaginal discharge more often than when they are not pregnant. This disorder is caused by poor hygiene of the genital organs. Knowledge is an important component in shaping a person's behavior. This research aims to determine the effectiveness of audio-visual media in increasing pregnant women's knowledge about vulva hygiene. This research uses a quantitative method, pre-experiment, one group pre-posttest. The sample used was 36 respondents using an accidental sampling technique. Bivariate analysis used the Wilcoxon test. There was an increase in the average knowledge score of pregnant women after being given audio-visual media about vulva hygiene with a p value <0.001. This educational media can be used by health facilities to provide education to pregnant women. Suggestions from researchers for research sites can utilize audio-visual media during health education, especially to pregnant women regarding vulva hygiene.